2016
DOI: 10.1109/tim.2016.2588586
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the Most Suitable Decomposition Filter for the Measurement of Fluctuating Harmonics

Abstract: Abstract-The proliferation of non-linear loads in both industrial and residential distribution grids leads to undesirable non-sinusoidal and fluctuating harmonic pollution on voltage and current waveforms. New analysis tools, such as wavelets, are being used to overcome the problems posed by the use of the Fourier Transform when analyzing complex waveforms. Nevertheless, the selection of the wavelet basis must be done carefully to minimize spectral leakage due to the non-exact frequency discrimination. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…In this paper, it is shown that this can be achieved by an accurate study of the WPD implementation. The novel algorithm hereafter presented is the continuation of the work performed by the authors in [26], where a detailed study was conducted to define a methodology for the selection of the most suitable filter and convolution technique for WPD applied to power systems' harmonics. The methodology proposed in [26] is here employed to develop and characterize a complete measurement method.…”
Section: Characteristics Of the Proposed Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, it is shown that this can be achieved by an accurate study of the WPD implementation. The novel algorithm hereafter presented is the continuation of the work performed by the authors in [26], where a detailed study was conducted to define a methodology for the selection of the most suitable filter and convolution technique for WPD applied to power systems' harmonics. The methodology proposed in [26] is here employed to develop and characterize a complete measurement method.…”
Section: Characteristics Of the Proposed Methodsmentioning
confidence: 99%
“…The novel algorithm hereafter presented is the continuation of the work performed by the authors in [26], where a detailed study was conducted to define a methodology for the selection of the most suitable filter and convolution technique for WPD applied to power systems' harmonics. The methodology proposed in [26] is here employed to develop and characterize a complete measurement method. In order to obtain the IEC frequency bands, up to at least the 50th order, a sampling rate of 6400 Hz is necessary, and seven levels of decomposition must be implemented.…”
Section: Characteristics Of the Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations